DESIGNING PROMOTIONAL VIDEOS FOR ADIVASA RESIDENTIAL COMPLEX USING THE DESIGN THINKING - Romadhon, Alfian; Prameswari, Nadia Sigi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The high dynamics of the Indonesian property market are influenced by a shift in consumer behavior towards digital media. In this context, Adivasa housing in Semarang presents a strong "Tropical Modern" concept. However, there is a gap between its product excellence and its marketing communication strategy, namely the absence of effective audio-visual media to touch the emotional needs of its target audience. As a solution, this research designs a strategic promotional video titled "The Meaning of a Home" using the audience-centered Design Thinking method. This process shifts the approach from a direct sale (hard-sell) to a subtle narrative (soft-sell) that focuses on warmth, comfort, and tranquility. The results of this research show that the Design Thinking method proved to be highly effective in creating a promotional medium that is not only visually appealing but also capable of building a strong emotional connection, and successfully aligning the marketing message with the core values offered by Adivasa Housing.